(untitled) (Veterinary Science, 2017)
Blood samples from ten Swedish dairy cows were taken one month before calving, at calving, and one month after calving. The blood concentration of vitamins A and E, and the trace element selenium (Se) were analysed, as well as the total and differential white blood cell counts,a nd the presenceo f CD62L and CD18 adhesionm oleculeso n blood neutrophils. The levels of vitamins A and E decreased significantly at calving, while whole blood Se increased Leukocytosisw as detectedat calving, explainedm ainly by neutrophilia.T he number of lymphocytest endedt o decreasea t calvrng.T he proportion of CD62L- neutrophilsd ecreased sisnlficantlv at this ttme